Enabling Power Systems With SQKD in Presence of Remote Nodes - Mariam Gado; Muhammad Ismail (IEEE Access)
Semi-quantum key distribution (SQKD) can be applied in power systems to share unconditionally secure keys between the power substations and the local controllers. Secret keys can be used for the encryption and decryption of control commands and measurements of power substations. This paper studies the allocation problem of a minimal number of trusted nodes, quantum servers with optimal source rates and fiber links on a pre-existing classical cyber layer of power system under the constraint of a minimal target key generation rate in the presence of an attacker for power systems with remote nodes. The optimization problem is formulated as a binary program that upgrades a pre-existing classical cyber layer of power system to support SQKD. Due to the complexity of the allocation problem, this paper develops algorithms based on Density-Based Spatial Clustering of Applications with Noise algorithm (DBSCAN), Dijksra’s algorithm and genetic algorithms. This research examined the proposed allocation strategy on the cyber layer of the IEEE 30-bus and the IEEE 118-bus test systems, since these systems have remote nodes. The work in the literature did not solve the systems with remote nodes, so this study modified two benchmarks to handle the remote nodes in order to compare with them. The results demonstrate that the target key generation rate can be achieved at different attack levels with a number of trusted nodes, quantum servers, source rates and a number of fiber links, that is 62.5% and 50%, respectively, less than a benchmark for the IEEE 30-bus and the IEEE 118-bus test systems. The results also demonstrate that the proposed solution requires 62.23% and 54.99% less number of quantum server, source rates and a number of fiber links compared to QKD solutions for the IEEE 30-bus and the IEEE 118-bus test systems, respectively.